PENGUJIAN FRAUD PENTAGON TERHADAP RESIKO FINANCIAL FRAUDULENT REPORTING - Meiliana Jaunanda; Daniel Peterson Silaban (Ultima Management : Jurnal Ilmu Manajemen, 2020)
The research to examine how much financial stability, financial target, external pressure, nature of industry, ineffective monitoring, rationalization, capability and oship have effect partially and simultaneously to fraud pentagon. The research subjects used were manufacturing companies and were listed on the BEI in the 2014-2018 period. The results of this study are financial stability has a significant influence on fraudulent financial reporting. Rationalization has a significant effect on fraudulent financial reporting. Arrogance partially has a significant influence on fraudulent financial statements, financial target, external pressure, nature of industry, ineffective monitoring, rationalization, capability and oship simultaneously have a significant effect on fraudulent financial statements. Key Words: Financial performance, Efficiency Operation, Firm Growth, Leverage, Fraud